Sonocrystallization of Conjugated Polymers with Ultrasound Fields - Xi, Yuyin (Soft Matter, 2018)
Ultrasound acoustic waves are demonstrated to assemble poly-3-hexylthiophene (P3HT) chains into nanofibers after they are fully dissolved in what are commonly considered to be ‘good’ solvents. In the absence of ultrasound, the polymer remains fully dissolved and does not self-assemble for weeks. UV-vis spectroscopy, ultra-small angle x-ray scattering (USAXS) and small angle neutron scattering (SANS) are used to characterize the induced assembly process and to quantify the fraction of polymer that forms nanofibers. It is determined that the solvent type, insonation time, and aging periods are all important factors affecting the structure and final concentration of fibers. The effect of changing polymer regio-regularity, alkyl chain length, and side chain to thiophene ratio are also explored. High intensity focused ultrasound (HIFU) fields of variable intensity are utilized to reveal the physical mechanisms leading to nanofiber formation, which is strongly correlated to cavitation events in the solvent. This in-situ HIFU cell, which is designed for simultaneous scattering analysis, is also used to probe for structural changes occurring over multiple length scales using USAXS and SANS. The proposed acoustic assembly mechanism suggests that, even when dispersed in ‘good’ solvents such as bromobenzene, dichlorobenzene and chloroform, P3HT chains are still not in a thermodynamically stable state. Instead, they are stabilized by local energy barriers that slow down and effectively prevent crystallization. Ultrasound fields are found to provide enough mechanical energy to overcome these barriers, triggering the formation of small crystalline nuclei that subsequently seed the growth of larger nanofibers.